Rolling with the punches: a national electronic injury surveillance system database study of craniofacial injuries in boxing - Wolfe, E. M.; Pierrot, R. G.; Slavin, B. R.; Plotsker, E. L.; Samaha, G. J.; Gishen, K.; Thaller, S. R. (The Journal of Craniofacial Surgery, 2021)
Introduction: Boxing is a popular combat sport in which competitors may sustain high impact blows to the face. For this reason, they are at high risk for craniofacial injuries; however, data on facial injuries specific to boxing remains sparse. Studies on safety measures, such as headgear, to prevent such injuries in boxing have been inconclusive. Boxing is popular with a wide audience. However, there is no consensus on safety measures across different populations involved in boxing due to lack of data. The objective of this study is to characterize the demography and incidence of injury types of patients presenting to emergency departments with boxing-related craniofacial injuries on a national scale in order to facilitate the establishment of evidence-based safety guidelines for prevention of boxing-related injuries.